Digital Literacy Competencies of Mechanical Engineering Vocational Education Teacher Candidates - et al., Setuju (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The era of the Industrial revolution 4.0 collaborates on cyber technology and automation technology. Rapid changes due to the 4.0 industrial revolution, require anticipatory steps by the government through increasing the quality of education. Preparing a great generation who has competencies as capital to anticipate the 4.0 industrial revolution, the 21st-century learning education. One of the competencies expected for 21st-century learning is digital literacy skills. Therefore, this study aims to determine the ability of prospective teachers prepared by the Mechanical Engineering Vocational Study Program, Sarjanawiyata University. The population of prospective teachers is students who have implemented teaching practices in schools in the 2019/2020 school year. Quantitative research with descriptive method approach. Data analysis with the percentage of students who use and integrate Information and Communication Technology (ICT) in learning during practical field experience (PPL). The results obtained conclude that digital literacy skills need to be improved, because students in their learning rarely (50%) use and integrate ICT in learning. Because with digital literacy skills students can design learning that facilitates students to think critically, creatively, and innovatively.